1996
DOI: 10.1002/(sici)1097-0274(199607)30:1<62::aid-ajim10>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem auditory evoked potentials in individuals exposed to long-term low concentrations of toluene

Abstract: Brainstem auditory evoked potentials (BAEPs) were examined in 49 workers employed in a printing press, who were occupationally exposed to low concentrations of toluene for an average of 20.3 years, and in 59 subjects in a control group. In the group of exposed workers, a significant decrease was found in all wave amplitudes examined, a significant prolongation of PI wave latency, and an increased interval of interpeak latencies (P3–P5), indicating that the extramedullary and high medullary part of the auditory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 5 publications
0
17
0
2
Order By: Relevance
“…Therefore, the ABR findings obtained in the present study suggest that the workers exposed to gasoline have auditory nerve dysfunction, as well as central auditory nervous system dysfunction involving brainstem. Dysfunction involving the auditory pathway in brainstem was also reported in a study of gasoline station workers as well as in workers exposed to solvents (Abbate et al 1993;Vrca et al 1996;Prasher et al 2005;Gopal 2008;Ju arez-P erez et al 2014;Fuente, McPherson and Cardemil 2013).…”
Section: Auditory-evoked Potentialsmentioning
confidence: 61%
See 2 more Smart Citations
“…Therefore, the ABR findings obtained in the present study suggest that the workers exposed to gasoline have auditory nerve dysfunction, as well as central auditory nervous system dysfunction involving brainstem. Dysfunction involving the auditory pathway in brainstem was also reported in a study of gasoline station workers as well as in workers exposed to solvents (Abbate et al 1993;Vrca et al 1996;Prasher et al 2005;Gopal 2008;Ju arez-P erez et al 2014;Fuente, McPherson and Cardemil 2013).…”
Section: Auditory-evoked Potentialsmentioning
confidence: 61%
“…Significantly longer ABR latencies for workers exposed to solvents have been observed (Abbate et al 1993;Vrca et al 1996;Fuente, McPherson, and Cardemil 2013;Ju arez-P erez et al 2014) but not always for the same waves. The mean latencies of waves I, III and V (Abbate et al 1993;Vrca et al 1996), I-III, III-V and I-V IPL (Abbate et al 1993), and III-IV IPL (Vrca et al 1996) were significantly longer for the exposed group than for the CG. In other studies, the exposed group showed longer latencies than the CG in all ABR waves and IPL except for wave I latency (Fuente, McPherson, and ABR waves I, III and V are generated in the distal portion of the auditory nerve, cochlear nucleus, and in the lateral lemniscus, respectively (Moller 2013), and that prolonged III-V, or I-V IPLs are signs of brainstem involvement (Musiek, Shinn, and Jirsa 2007).…”
Section: Auditory-evoked Potentialsmentioning
confidence: 82%
See 1 more Smart Citation
“…11,23 Fuente et al have shown that workers exposed to a mixture of solvents (toluene, xylene and methyl ethyl ketone) may acquire central auditory dysfunction, as measured through a set of behavioral central auditory processing tests. 11 Other studies have found central auditory effects associated with solvent exposure (mainly toluene) through the use of electrophysiological measures such as the auditory brainstem response 1,27 and the P300 response. 18,26 In summary, solvents not only adversely affect the sensory organ of the auditory system (cochlea), as noise does, but also affect the central auditory structures.…”
Section: Introductionmentioning
confidence: 99%
“…Workers exposed to toluene obtained statistically significant higher absolute latencies and inter-peak latencies (IPL) between waves of the ABR (I-III IPL; I-V IPL; III-V IPL) than a non-exposed group of workers matched for gender and age (Abbate et al, 1993). Additional evidence of toluene-induced central auditory dysfunction in humans using ABR was shown by Vrca et al (1996). Workers exposed to low concentrations of toluene obtained a significant decrease in all wave amplitudes of auditory evoked potentials.…”
Section: Evidence Of the Adverse Effects Of Solvents On The Central Amentioning
confidence: 92%